Immunohistochemical Diagnostic value of Calretinin in Hirschprung Disease - Azis, Zainab; Cangara, M. Husni; Zainuddin, Andi Alfian; Wahid, Syarifuddin; Mariana, Nita; Miskad, Upik A. (Nusantara Medical Science Journal, 2023)
Introduction: Hirschsprung's disease (HD) is characterized by the absence of ganglion cells in Meissner's plexus and Auerbach's plexus which used to be assessed by histopathological examination using Hematoxylin and Eosin (H&E).  In some cases is difficult to assess ganglion cells, thus requiring additional examination in the form of calretinin immunohistochemistry to detect the presence of ganglion. Methods: The 59 samples of suspected HD  were analyzed by H&E staining followed by calretinin immunohistochemical staining. This study aimed to assess the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of calretinin in HD diagnostics. Results:  The immunohistochemistry of calretinin showed a good diagnostic value in detecting aganglionosis in patients with suspected HD with a sensitivity value = 97.7%; Specificity = 100%; Positive Presumptive Value (PPV) = 100%; Negative Presumptive Value (NPV) = 93.7%; Accuracy= 98.3%. Thus, calretinin immunohistochemistry can be relied upon as an additional method in the diagnosis of HD